2015
DOI: 10.1186/s12944-015-0049-7
|View full text |Cite
|
Sign up to set email alerts
|

A review of the effect of omega-3 polyunsaturated fatty acids on blood triacylglycerol levels in normolipidemic and borderline hyperlipidemic individuals

Abstract: Circulating levels of triacylglycerol (TG) is a recognized risk factor for developing cardiovascular disease, a leading cause of death worldwide. The Institute of Medicine and the American Heart Association both recommend the consumption of n-3 polyunsaturated fatty acids (PUFA), specifically eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), to reduce serum TG in hyperlipidemic individuals. Additionally, a number of systematic reviews have shown that individuals with any degree of dyslipidemia, eleva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
78
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(89 citation statements)
references
References 62 publications
(122 reference statements)
9
78
1
1
Order By: Relevance
“…The TAG lowering effects are variable depending on the daily intake of DHA [73]. When ≥4 g/day of n-3 PUFA is consumed, there is a 9%–26% reduction in circulating TAG, while a 4%–5% reduction occurs when 1–5 g/day of EPA and/or DHA are consumed [85]. In healthy male adults, fish oil or DHA-oil supplementation for 15 weeks lowers fasting plasma TAG concentrations and increases the plasma HDL2/HDL3 cholesterol ratio [72]; HDL3 content is associated with increased visceral fat deposition and impaired VLDL function [86].…”
Section: The Beneficial Physiological Effects Of N-3 Pufamentioning
confidence: 99%
See 2 more Smart Citations
“…The TAG lowering effects are variable depending on the daily intake of DHA [73]. When ≥4 g/day of n-3 PUFA is consumed, there is a 9%–26% reduction in circulating TAG, while a 4%–5% reduction occurs when 1–5 g/day of EPA and/or DHA are consumed [85]. In healthy male adults, fish oil or DHA-oil supplementation for 15 weeks lowers fasting plasma TAG concentrations and increases the plasma HDL2/HDL3 cholesterol ratio [72]; HDL3 content is associated with increased visceral fat deposition and impaired VLDL function [86].…”
Section: The Beneficial Physiological Effects Of N-3 Pufamentioning
confidence: 99%
“…Moreover, variation in a rate-limiting gene for PUFA synthesis, Δ 6-desaturase, can affect the prevalence of metabolic syndrome [59]. The lack of a consistent study design and variations in human responsiveness may be major limitations to assess the effects of n-3 PUFA and to establish a recommended dose for n-3 PUFA intake [85]. Hence, animal models in vivo and in vitro are required to reveal potential mechanisms for the n-3 PUFA effects.…”
Section: The Beneficial Physiological Effects Of N-3 Pufamentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with this finding, fish oil fed rats treated with the carcinogen azoxymethane (AOM) had reduced colon tumor incidence and multiplicity compared to Western diet fed controls [7, 18]. In addition, fish oils are known to have a triglyceride lowering effect [19], but the effects of fish oils on colon lipids are currently less well defined.…”
Section: Introductionmentioning
confidence: 97%
“…Much of the research in this area has been focused on marine lipidic compounds found in seafood such as unsaturated fatty acids ω-3 and ω-6, to which prevention of chronico-degenerative illnesses have been attributed (Burgos-Hernández et al, 2001;Farzaneh-Far et al, 2010;Shahidi & Miraliakbari, 2004;Ewaschuk et al, 2012;Chen et al, 2015;Darghosian et al, 2015;Leslie et al, 2015;Eide et al, 2016). However, little attention has been given to the chemical composition of seafood wastes (skin, viscera, and fish heads) as a source of biologically active molecules.…”
Section: Introductionmentioning
confidence: 99%